Математичне моделювання розподілу корисних копалин за допомогою інтерлінації функцій трьох змінних - Литвин, О.М.; Штепа, Н.І. (Видавничий дім "Академперіодика" НАН України, 2009)
Будуються i дослiджуються оператори iнтерлiнацiї (blending function interpolation) функцiї 3-х змiнних зi слiдами цiєї функцiї на системi прямих, паралельних осi Oz i нерегулярно розмiщених в областi дослiдження. При побудовi цих операторiв використовуються узагальненi формули Шепарда i Тейлора–Рвачова. The operators of interlineation of a function of three variables (blending function interpolation) with traces of this function on the system of straight lines parallel to the Oz axis are constructed and investigated. These straight lines are irregularly placed in the region under study. On the construction of these operators, the generalized Shepard’s and Taylor-Rvachev’s formulas are used.